Implementing a new living concept for persons with dementia in long-term care: evaluation of a quality improvement process - Suzanne Portegijs; Adriana Petronella Anna van Beek; Lilian Huibertina Davida van Tuyl; Cordula Wagner (BMC, 2024)
Abstract Background Improving quality of nursing home care for residents is a constant focus of stakeholders involved within quality improvement projects. Though, achieving change in long-term care is challenging. Process evaluations provide insight into the nature, exposure and experiences of stakeholders and influencing mechanisms for implementation. The aim of this study is to gain insight into the process and facilitating and hindering mechanisms of implementing a quality improvement project that seeks to create a dementia-friendly community with a nursing home at its core. Methods For the process evaluation we planned a case study design with an ethnographic approach. Various research methods were used: qualitative observations, focus groups, interviews and questionnaires for various stakeholders and document review. Data collection and analyses in this study is based on the Consolidated Framework for Implementation Research. Results Four main lessons were learned. Firstly, nursing staff are crucial to achieve more freedom for residents. Secondly, high-impact changes in daily care need strong and sustainable focus from the care organisation. Thirdly, dementia-friendly societies should be deployed from multiple actors, which entails long-term collaborations with external stakeholders. Fourthly, the transition to a dementia-friendly society requires meeting spaces for and a focus on both residents and people from the community. Consequently, local residents are shifting from external to internal stakeholders, extending beyond the regular involvement of informal carers and volunteers within the nursing home. Conclusions Nursing homes are part of the local community and provide opportunities to collaborate on a dementia-friendly society. However, the change that is required (promoting freedom, residents' autonomy and the redesign of care processes) is complex and influenced by various mechanisms. Understanding these mechanisms can benefit other care organisations that strive to implement a similar initiative.